Optimization of Debtor Information Systems in Pressing Problem Financing in Some Syari'ah BPR in Aceh Province - Yusuf, Zulfan; Rizal, Syamsul (International Journal of Management Science and Information Technology, 2021)
Article 1 paragraph (1) of Law Number 10 the Year 1998 states that banking is a financial institution that collects funds from the public in the form of savings, time deposits, and demand deposits and which can be equated with them. Furthermore, it is channeled back to the public in the form of credit (financing in the Syari'ah Bank), with the aim of achieving people's welfare. Furthermore, based on Law Number. 21 of 2008 explains that a Syari'ah bank is a bank financial institution that runs its operations in a Shari'ah manner. One of the duties of banking institutions is to channel credit/financing to the public so that it can spur economic growth in the informal sector in the Region and National in the context of the Unitary State of the Republic of Indonesia. In the provision of credit/financing, it is not uncommon for fraudulent (internal) practices carried out by loan officers (AO / FO), finance staff, so that they can worsen Non-Performing Loans / Financing, which in turn can undermine the bank's own capital. The debtor information system is a strategic effort to minimize the occurrence of non-performing loans so that the quality of financing can still be controlled at all times. The collectability of financing can also be used as a benchmark in increasing the competitiveness and selling value of a bank. The purpose of this study is to determine the extent to which banking institutions, in this case, the Islamic People's Financing Bank have implemented these provisions, what obstacles were found, and efforts to resolve them. This type of research is an Empirical Juridical, namely examining the Regulations governing Anti Money Laundering (APU) and the Prevention of Terrorism Funding (PPT) as well as Debtor Information within the scope of the financing process in several Sharia Rural Banks (BPRS) in Aceh Province. Based on research in eleven Sharia People's Financing Banks in Aceh Province, it is known that 68.3% have operational procedures (sop) on AML and CFT and run them well, while 31.7% have AML and CFT regulations, but have not implemented them optimally. . The reason why this provision has not been implemented optimally is that more intensive socialization is needed to related parties, including bank debtors, considering that debtors are prime customers in growing a bank.